Involvement of tolQ and tolR genes in Edwardsiella ictaluri virulence. (November 2016) - Abdelhamed, Hossam; Lu, Jingjun; Lawrence, Mark L.; Karsi, Attila
Abstract: Edwardsiella ictaluri is a Gram-negative intracellular facultative pathogen causing enteric septicemia of channel catfish (ESC). The Tol system, consisting of four envelope proteins TolQ, TolR, TolA, and TolB, are required for colicin import and contributes to bacterial virulence in several pathogenic bacteria. However, the Tol system and its importance in E. ictaluri virulence have not been investigated. Here we present construction and evaluation of the E. ictaluri TolQ, TolR and TolQR mutants ( Ei Δ tolQ, Ei Δ tolR, and Ei Δ tolQR ). The Tol mutants were developed using in-frame gene deletion and their attenuation and vaccine efficacy were determined in catfish fingerlings. The Ei Δ tolQ, Ei Δ tolR, and Ei Δ tolQR mutants showed reduced virulence in catfish (28.93%, 19.70%, and 39.82% mortality, respectively) compared to wild type (46.91% mortality). Further, vaccination with these mutants protected catfish against subsequent wild-type infection. This study suggests that the Tol system contributes to E. ictaluri virulence in catfish.